Half-sandwich ruthenium (II) p-cymene complexes based on organophosphorus ligands: Structure determination, computational investigation, in vitro antiproliferative effect in breast cancer cells and antimicrobial activity. (1st August 2021) - Klaimanee, Ekkapong; Nhukeaw, Tidarat; Saithong, Saowanit; Ratanaphan, Adisorn; Phongpaichit, Souwalak; Tantirungrotechai, Yuthana; Leesakul, Nararak
Graphical abstract: Abstract: Three novel organometallic ruthenium(II) p- cymene complexes based on organophosphorus ligands, [Ru2 ( p -cymene)2 (dppp)Cl4 ] (1), [Ru2 ( p -cymene)2 (dpppe)Cl4 ] (2 ), and [Ru2 ( p -cymene) (dppbe)Cl4 ] (3 ), were successfully synthesized by complexation of [RuCl( p -cymene) ( μ -Cl)]2 dimer with bis(diphenylphosphino)propane (dppp), bis(diphenylphosphino)pentane (dpppe), and bis(diphenylphosphino)benzene (dppbe). Complexes 1 and 2 were homo-binuclear metallic complexes comprising two distorted tetrahedral Ru(II) centers with η 6 - p -cymene, two chloro ligands, and the related P-donor ligand. On the other hand, complex 3 was a half-sandwich homo-binuclear metallic complex comprising a distorted tetrahedral Ru(II) center and an octahedral Ru(II) center. The complexes were characterized by single crystal x-ray diffraction, 1 H NMR, ES-MS, FTIR, elemental analysis, and density functional theory. The complexes exhibited in vitro anticancer activity towards MCF-7, HCC1937, and MDA-MB-231 human breast cancer cell lines, with a much higher sensitivity than cisplatin. Complex 1 was especially effective towards these cancer cell lines, giving IC50 values of 0.3520 ± 0.02, 0.5386 ± 0.01 and 0.8944 ± 0.03 μM, respectively. Moreover, all complexes showed significant activity against the Gram-positive bacteria, Staphylococcus aureus ATCC25923 (SA) and methicillin–resistant Staphylococcus aureus (MRSA). Complex 2 shows the greatest MIC/MBC values of 1/8 μg.mL −1 and 0.5/8 μg.mL −1 for SA and MRSA inhibition, respectively. Interesting antifungal activity and antifilamentous fungal activity was also observed in complex 2.